(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Portal hypertension (PH) is a major complication of cirrhosis, associated with significant morbidity and mortality. Early and accurate detection is essential for effective management, with ultrasonography (US) emerging as a valuable non-invasive diagnostic tool. This review systematically evaluates the accuracy of ultrasonography for detecting portal hypertension in cirrhotic patients by analyzing studies published between 2015 and 2025. Objectives: To assess the diagnostic performance of ultrasonography in detecting portal hypertension, focusing on sensitivity, specificity, and overall diagnostic accuracy. Methods: A systematic review was conducted following PRISMA guidelines. Studies were identified through PubMed, Google Scholar, and Springer databases. Original research articles published between 2015 and 2025 that compared ultrasonography with reference standards such as hepatic venous pressure gradient (HVPG) or liver biopsy were included. Key outcomes assessed were sensitivity, specificity, and diagnostic accuracy. Results: The included studies demonstrated variable results across ultrasonographic techniques. Sensitivity ranged from 70% to 90%, with the highest sensitivity reported in studies using elastography and contrast-enhanced ultrasound (CEUS). Specificity ranged from 60% to 92%, with studies incorporating advanced imaging techniques showing higher specificity. Studies utilizing elastography and CEUS reported superior diagnostic accuracy compared to conventional gray-scale ultrasound, with overall diagnostic... Conclusion: Ultrasonography, enhanced by elastography and CEUS, is a reliable non-invasive tool for detecting portal hypertension in cirrhotic patients, showing high sensitivity. However, specificity varies, and further research is needed to optimize diagnostic criteria and combine imaging techniques for improved accuracy.